Making life meaningful - Zopa, Thubten; Ribush, Nicholas (Boston : Lama Yeshe Wisdom Archive, 2001)
"This book starts with a public talk emphasizing the practice of compassion and guru devotion and follows with chapters on practicing bodhicitta in daily life, purification with the Thirty-five Buddhas and dedication of merit"--Provided by publisher.
Includes bibliographical references (p. [131]-132).
Keywords: Spiritual life -- Buddhism; Spiritual life